Depiction of a Surasundari on the northern wall of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
On the northern wall of the garbhagriha (sanctum sanctorum), there is a finely carved depiction of a surasundari (celestial damsel). She wears an intricate bun as her hairstyle and stands tall and slender, adorned with jewellery. One of her hands is damaged, while the other rests on her thigh. Alongside her, there is a portrayal of an ascetic on the same wall. He stands slightly turned to his left, sporting a jatabhara (braided hairdo) on his head and a lengthy moustache. Although erosion has obscured the features of his face, the elongated earlobes and a rudraksha (dried stones or seeds of Elaeocarpus ganitrus) armband are noticeable. One of his hands grasps a pot, and the other delicately positions fingers atop it. Notably, his phallus is exposed in this depiction. It is worth observing that both the ascetic and the surasundari are depicted nude, symbolizing different natures and representing opposing symbolism of mundane and spiritual.